2022
DOI: 10.7717/peerj.13414
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of fibrillin (FBN) gene family in tomato (Solanum lycopersicum L.)

Abstract: Background Fibrillin (FBN) proteins are widely distributed in the photosynthetic organs. The members of FBN gene family play important roles in plant growth and development, and response to hormone and stresses. Tomato is a vegetable crop with significantly economic value and model plant commonly used in research. However, the FBN family has not been systematical studied in tomato. Methods In this study, 14 FBN genes were identified in tomato genome by Pfam and Hmmer 3.0 software. ExPASy, MEGA 6.0, MEME, GSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Similar to the up-regulation of PSY and FBN6 genes during Arabidopsis deetiolation (Fig. 4A), the burst in carotenoid synthesis that takes place during tomato fruit ripening is also associated with increased expression of genes encoding the corresponding PSY and FBN6 homologues (Barja et al, 2021; Sun et al, 2022). This observation suggests that FBN6-dependent promotion of PSY activity and carotenoid biosynthesis might not be restricted to chloroplasts but also occur in chromoplasts.…”
Section: Resultsmentioning
confidence: 59%
“…Similar to the up-regulation of PSY and FBN6 genes during Arabidopsis deetiolation (Fig. 4A), the burst in carotenoid synthesis that takes place during tomato fruit ripening is also associated with increased expression of genes encoding the corresponding PSY and FBN6 homologues (Barja et al, 2021; Sun et al, 2022). This observation suggests that FBN6-dependent promotion of PSY activity and carotenoid biosynthesis might not be restricted to chloroplasts but also occur in chromoplasts.…”
Section: Resultsmentioning
confidence: 59%
“…Dirigent genes ( DIRs ) encode proteins that act as crucial regulators of plant lignin biosynthesis and play essential roles in plant growth, development, as well as biotic and abiotic stress response [ 1 ]. The DIR protein was initially identified by Davin et al (1997) in Forsythia suspensa , the DIR protein plays a crucial role in directing stereoselective bimolecular phenoxy radical coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Gene function determines the extent to which a gene is expressed in various tissues and at various times during development. Several research works have reported the effects of abiotic stress on FBNs , and it is evident that they are regulated by a wide range of biological and environmental factors [ 10 , 11 , 12 , 25 ]. The expression of cis -regulatory elements in downstream genes is regulated by transcription factors, which play a role in a wide range of biological activities [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The FBN protein family is composed of 12 sub-families. These sub-families have been identified in a wide range of organisms, i.e., from algae to higher plants, including wheat, Arabidopsis, tomato, and rice [ 10 , 11 ]. In wheat, besides being expressed in different tissues and developmental stages, TaFBNs are also expressed in response to biotic (stripe rust) and abiotic (drought, cold and heat) stresses [ 10 ].…”
Section: Introductionmentioning
confidence: 99%